Simulation and optimization of fatty acid extraction parameters from Nannochloropsis sp. using supercritical carbon dioxide - Kim, Ivander Jonathan; Aris Romadhon Subkhan; Rakha Putra Prasetya; Yuswan Muharam (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Microalgae, which are rich in fatty acids, have potential applications in various sectors such as bioenergy, health, food, and biomaterials. The Supercritical Fluid Extraction (SFE) method is commonly used to extract microalgae. This research estimated the process parameters of desorption rate constant (kd) and binary diffusion coefficient (DAB) for SFE fatty acid from Nannochloropsis sp. using a mathematical model called as hot sphere diffusion. Desorption models were used to model the release of fatty acids into the solvent (supercritical carbon dioxide). The parameter estimation process was conducted at temperatures of 313 and 333 K and pressures of 12.5, 20, and 30 MPa. The value of kd increased with increasing pressure and temperature and DAB values were obtained at varying pressures and temperatures.